Organizational Culture In Educational Institutions - Muhammad Saparuddin; Purnomo Sidik (PT. Berkah Smart Academica, 2024)
This research investigates the role of organizational culture in the context of educational institutions through a literature study approach. Through a thorough analysis of the relevant literature, we outline the core elements of organizational culture, organizational functions, goals, and benefits of organizations in an educational context. We explore how organizational culture shapes the identity and unique characteristics of educational institutions, influencing interactions between staff members, students, and other stakeholders. In addition, we discuss the implications of organizational culture on the effectiveness of educational institutions, including performance improvement, innovation, and adaptation to environmental change. Our analysis also highlights the impact of organizational culture on students' learning experiences, social interactions and the quality of educational services. The results of this study underscore the importance of a deep understanding of organizational culture in shaping productive and inclusive learning environments in educational institutions and provide directions for further educational management research and practice.